PROFIL GANGGUAN PENDENGARAN PADA PEMUSIK DI KOTA MANADO - Lauw, Riscky B. (e-Biomedik, 2013)
Abstract: Hearing loss due to noise (Noise Induced Hearing Loss - NIHL) is hearing impairment, either part or all, loss, irreversible, occur in one or both ears, can be mild, moderate or severe, occurs because of exposure to the constant noise from the environment. The musician is one of the communities that are susceptible to noise induced hearing loss. Musicians had considerable exposure to noise. Most musicians have a hearing loss in varying degrees. The research objective is to determine the profile of hearing loss in the musicians in Manado, researching threshold musical sound that can cause hearing loss, and looking for a relationship with duration of music exposure to hearing loss. Research is explanatory research, analytical research methods and cross-sectional approach. Research conducted on hearing music group in the City of Manado. The study involved 30 people with the details of 15 respondents guitar players and 15 drummers. The result is: The degree of noise in the gym most of the 110-130 dB, experienced by 46.7% of respondents, mostly studied band of men which is about 90%. Hearing loss is the most followed by drummer and then gitarist, 46.7% and 36.6%, respectively; based upon long exposure to music,> 5 years 46.6%, based on length of exercise per day, more in the 3-4 hours it is 40%. Based on the result of the study, there is a relationship between noise exposure and hearing loss in musicians in the city of Manado. The noise level, exposure time per day, duration of exposure and vulnerability of respondents, closely related to hearing loss disorder the musicians in this study. Keywords: Hearing loss, the noise level, duration of exposure, musicians.Abstrak: Noise induce hearing loss (NIHL) atau gangguan pendengaran akibat kebisingan adalah gangguan pendengaran baik sebagian atau seluruh pendengaran, bersifat menetap, terjadi pada satu atau dua telinga, dapat bersifat ringan, sedang atau berat, terjadi karena paparan bising yang terus-menerus dari lingkungan. Pemusik adalah salah satu komunitas yang rentan terhadap gangguan pendengaran akibat bising. Pemusik mengalami paparan suara yang begitu besar. Kebanyakan pemusik mengalami gangguan pendengaran dalam berbagai derajat. Tujuan penelitian adalah untuk mengetahui profil gangguan pendengaran pemusik di kota manado, meneliti ambang batas suara musik yang dapat menyebabkan gangguan pendengaran serta mencari hubungan lama paparan musik dengan gangguan pendengaran. Penelitian bersifat Explanatory Research, dengan metode penelitian analitik dan pendekatan cross sectional. Penelitian gangguan pendengaran dilakukan pada kelompok musik di Kota Manado. Penelitian ini melibatkan 30 orang responden dengan rincian 15 pemain gitar dan 15 pemain drum. Hasil yang diperoleh adalah: Derajat kebisingan pada tempat latihan paling banyak antara 110-130 dB, dialami oleh 46,7 % responden, personil band yang diteliti kebanyakan laki-laki yaitu sekitar 90 %. Gangguan pendengaran terbanyak adalah pemain drum diikuti oleh gitaris 46,7 % and 36,6 %. Berdasarkan lama paparan musik, > 5 tahun 46,6 %; berdasarkan lama latihan per hari, lebih banyak pada 3-4 jam yaitu 40 %. Berdasarkan hasil penelitian kesimpulannya, terdapat hubungan antara paparan kebisingan dan gangguan pendengaran pada pemusik di Kota Manado. Tingkat kebisingan, waktu paparan perhari, lama terpapar serta kerentanan responden, berhubungan erat dengan pendengaran pada pemusik pada penelitian ini. Kata kunci: Gangguan pendengaran, tingkat kebisingan, lama paparan, pemusik.